Molecular epidemiology of vancomycin-resistant Enterococcus faecium: A prospective, multicenter study in South American hospitals (2010)
Enterococcus faecium has emerged as an important nosocomial pathogen worldwide, and this trend has been associated with the dissemination of a genetic lineage designated clonal cluster 17 (CC17). Enterococcal isolates were collected prospectively (2006 to 2008) from 32 hospitals in Colombia, Ecuador, Perú, and Venezuela and subjected to antimicrobial susceptibility testing. Genotyping was performed with all vancomycin-resistant E. faecium (VREfm) isolates by pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing. All VREfm isolates were evaluated for the presence of 16 putative virulence genes (14 fms genes, the esp gene of E. faecium [espEfm], and the hyl gene of E. faecium [hylEfm]) and plasmids carrying the fms20-fms21 (pilA), hylEfm, and vanA genes. Of 723 enterococcal isolates recovered, E. faecalis was the most common (78%). Vancomycin resistance was detected in 6% of the isolates (74% of which were E. faecium). Eleven distinct PFGE types were found among the VREfm isolates, with most belonging to sequence types 412 and 18. The ebpAEfm-ebpBEfm-ebpCEfm (pilB) and fms11-fms19-fms16 clusters were detected in all VREfm isolates from the region, whereas espEfm and hylEfm were detected in 69% and 23% of the isolates, respectively. The fms20-fms21 (pilA) cluster, which encodes a putative pilus-like protein, was found on plasmids from almost all VREfm isolates and was sometimes found to coexist with hylEfm and the vanA gene cluster. The population genetics of VREfm in South America appear to resemble those of such strains in the United States in the early years of the CC17 epidemic. The overwhelming presence of plasmids encoding putative virulence factors and vanA genes suggests that E. faecium from the CC17 genogroup may disseminate in the region in the coming years. Enterococci are now recognized as important nosocomial pathogens worldwide and in the United States are ranked as the second most common cause of nosocomial infections, after staphylococci (14). The two most common enterococcal species isolated from clinical samples are Enterococcus faecalis and E. faecium; however, the proportions of isolates of these two species have dramatically changed in the last decade. Whereas up until the early to mid-1990s E. faecalis was the overwhelmingly predominant species isolated in U.S. hospitals (37), by 2008, the proportion of nosocomial E. faecalis/E. faecium strains was ca. 1.5:1, and there was an important increase in the incidence of E. faecium nosocomial infections (14). Moreover, more than 80% of E. faecium isolates currently recovered from U.S. hospitals are resistant to vancomycin, and virtually all of them (>90%) exhibit ampicillin resistance (14). On the contrary, the prevalence of vancomycin resistance in E. faecalis remains low (<7% of isolates), and ampicillin resistance continues to be extremely rare. This change in the epidemiology of enterococcal infections has been attributed to the increased ability of a genogroup of E. faecium (designated clonal cluster 17 [CC17]) to colonize the gastrointestinal tract of humans, cause disease (37), and exhibit high levels of resistance to most antienterococcal antibiotics. Several virulence and colonizing factors have been postulated to explain this increased virulence (4, 25, 28) and include the following: (i) the presence of an intact acm gene, which encodes a collagen adhesin and which has been associated with the pathogenesis of endocarditis in members of CC17 (25); (ii) the esp gene of E. faecium (espEfm), which codes for an enterococcal surface protein, which has been shown to play a role in biofilm formation (12), and which transiently aggravates experimental urinary tract infection (18); (iii) the fms (E. faecium surface protein-encoding) genes, which encode cell wall-anchored proteins, including subunits of the enterococcal pili (13, 31); and (iv) the hyl gene of E. faecium (hylEfm; which encodes a putative glycosyl hydrolase), which is carried by transferable plasmids that have been shown to increase the ability of a laboratory strain of E. faecium to colonize the gastrointestinal tracts of mice and also enhance the virulence of a commensal strain of E. faecium in experimental peritonitis (4, 28). In South America (Brazil and Argentina), vancomycin-resistant (VR) enterococcal infections have been described since 1998 (9, 20). In a prospective multicenter surveillance study conducted in 2003, the prevalence of VR among enterococci in Colombia was found to be lower (9.7%) than that in the United States (1), and the isolation of similar percentages of VR enterococci has been described more recently (21). Although the emergence of E. faecium CC17 has been documented in Brazil, Chile, and Paraguay (16, 19, 39), prospective studies have not been performed and limited data regarding the presence of the potential virulence determinants of CC17 E. faecium (including hylEfm-containing plasmids) in South America are available. Thus, we performed a multinational, multicenter prospective surveillance study with the aim of characterizing the population genetics of enterococci circulating in the northern region of South America. Clinical isolates (excluding colonizing isolates) were collected prospectively from 32 hospitals in four countries (Colombia, Ecuador, Perú, and Venezuela) and were further characterized at the molecular level.